PELATIHAN STRATEGI PEMASARAN PELAKU UMKM DALAM PEMANFAATAN GEDEBOK PISANG DI KUAMANG KUNING - Widyastuti, Ira; Sasmita Rusnaini; Deni Handani; Syah Amin Albadry; Ha Esdhona (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Abstract Marketing strategy is a way to achieve sustainable competitive advantage for companies that produce goods and services. Marketing strategy can be considered as one of the foundations for creating an overall business plan. In a global economy however, they often face challenges in maintaining their products in an increasingly tight market. In this article, we analyze various effective marketing strategies for UMKM to overcome increasingly fierce competition and maintain their competitive advantage. The objectives of this activity include finding out what marketing strategies can be used to increase competitiveness and maintain their products in the face of increasingly fierce competition, as well as knowing the obstacles so that they can provide the right solutions to handle them. Apart from that, the aim of this activity is to encourage community innovation and creativity. Type and Research Approach, namely qualitative. A qualitative approach is an understanding based on a methodology that investigates a social and human phenomenon. Data collection techniques were carried out using interviews, observation and documentation. This research was carried out in Bangun Harjo Village, Pelepat Ilir District, Bungo Regency. The researcher focused on the PMD (Village Community Empowerment) case study of Bangun Harjo Village Kuamang Kuning. Keywords: Training, Strategy, Marketing, UMKM